Semi-commercial hot water treatments for control of bull’s eye rot of apples - Hasna, Luna; Everett, Kerry R.; Vergara, Michelle J.; Pushparajah, I.P. Shamini; Wood, Peter N.; Fisher, Brent M.; Ramos, Lucia R.; Middleditch, Carol; Olsson, Shane; Nangul, Agam; Cho, Jung Ook; Woolf, Allan B. (New Zealand Plant Protection, 2019)
Bull’s eye rot (BER) of apples is caused by a postharvest fungal pathogen (Phlyctema vagabunda syn. Neofabraea alba). Previous laboratory experiments found hot water treatments (HWT) resulted in a significant reduction of BER incidence for artificially inoculated fruit so the feasibility of HWT to control naturally infected fruit in a semi-commercial trial was tested. One bin (1934 fruit) of naturally infected ‘Scired’ apples was harvested from a Hawke’s Bay orchard with a known high incidence of BER, then placed in a coolstore for 1 week until treated. All fruit were passed through a high-pressure water blaster then air dried. Approximately half the contents of the bin (1034 fruit) were packed into Friday trays in apple boxes with a plastic polyliner. The other half (900 fruit) were treated for 2 min with hot water at 51°C in a semi-commercial hot water bath before packing. All fruit were then coolstored for 20 weeks before assessment for BER. This HWT resulted in a 6-fold reduction of BER incidence so was an effective treatment for BER in a semi-commercial test.